Hybridoma-inspired strategy crafts tailored multifunctional exosomes for precision therapy - Zhufeng Dong; Tieying Yin; Zhiqin Deng; Hang Zou; Lei Kuang; Yang Wang; Wen Shi; Mengwei Han; Siqing Zhu; Zheng Wang; Xiaoye Hu; Yazhou Wang (Proceedings of the National Academy of Sciences, 2025)
Engineering functional exosomes represents a cutting-edge approach in biomedicine, holding the promise to transform targeted therapy. However, challenges such as achieving consistent modification and scalability have limited their wider adoption. Herein, we introduce a universal and effective strategy for engineering multifunctional exosomes through cell fusion. The hybrid-cell-derived exosomes could combine the functional properties of both parental cells and be readily produced by passaging. This method enables customization and large-scale production of exosomes with specific functionalities, potentially advancing precision therapies across a wide array of diseases. As demonstrated in Alzheimer’s disease (AD) models, exosomes derived from hybrid cells (HCs) (H/Exos) of mesenchymal stem cells (MSCs) and neutrophils efficiently targeted AD-affected areas via LFA-1/ICAM-1 and improved the cognition of AD mice. Beyond directly promoting neural repair and inhibiting inflammation, we surprisingly found that H/Exos increased microglia abundance, modulated microglia gene expression, enhanced the endocytic and lysosomal function, and promoted microglial phagocytic phenotypic differentiation to clear Aβ. This hybridoma-inspired strategy offers a versatile and practical way to engineer exosomes with desired therapeutic functions, representing a promising direction for personalized therapies.